'Picking up the neighbours' waste': migration of Bangladeshi villagers to India metropolises. (2nd January 2020) - Percot, Marie
ABSTRACT: From a small area of the South West of Bangladesh, thousands of landless farmers cross the border with their family in order to work in the informal sector, mostly in Delhi and Bangalore: as waster pickers for the men, as maids for the women. Based on two ethnographic fieldworks in the villages of origin, this article intends to highlight the reasons leading to this migratory movement, the way this migration is organized and its consequences for the families. In a context where, in India, Bangladeshi migration is mostly felt as a threat, it also analyses the process of hypervisibility/invisibility to which these migrants are subjected to and the effects that deportability – or actual deportation – have on their life. At last, it examines how migrants experience the discrepancy between the way they see themselves and the way they are largely considered by the Indian authorities and broaden society.